2009
DOI: 10.1200/jco.2008.20.5278
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival in Metastatic Colorectal Cancer Is Associated With Adoption of Hepatic Resection and Improved Chemotherapy

Abstract: A B S T R A C T PurposeFluorouracil/leucovorin as the sole therapy for metastatic colorectal cancer (CRC) provides an overall survival of 8 to 12 months. With an increase in surgical resections of metastatic disease and development of new chemotherapies, indirect evidence suggests that outcomes for patients are improving in the general population, although the incremental gain has not yet been quantified. MethodsWe performed a retrospective review of patients newly diagnosed with metastatic CRC treated at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
761
1
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,193 publications
(809 citation statements)
references
References 23 publications
22
761
1
25
Order By: Relevance
“…The development of new surgical approaches, together with an increasing use of the perioperative systemic therapy, have led to an increase of the percentage of patients potentially eligible for curative liver resection (Rolfo et al, , 2013Bronte et al, 2015Bronte et al, , 2013. In most series, up to 25% of patients presenting with stage IV CRC undergo hepatic resection (Kopetz et al, 2009), with reported 5-year survival rates up to 50% (Taylor et al, 2010;Choti et al, 2002;Chua et al, 2011). However over one-half of patients will develop recurrence within 2 years (de Jong et al, 2009;Fong et al, 1999;Nordlinger et al, 1996), not getting any long-term survival benefit from hepatic resection.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new surgical approaches, together with an increasing use of the perioperative systemic therapy, have led to an increase of the percentage of patients potentially eligible for curative liver resection (Rolfo et al, , 2013Bronte et al, 2015Bronte et al, , 2013. In most series, up to 25% of patients presenting with stage IV CRC undergo hepatic resection (Kopetz et al, 2009), with reported 5-year survival rates up to 50% (Taylor et al, 2010;Choti et al, 2002;Chua et al, 2011). However over one-half of patients will develop recurrence within 2 years (de Jong et al, 2009;Fong et al, 1999;Nordlinger et al, 1996), not getting any long-term survival benefit from hepatic resection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of CRC is increasing, mortality has decreased due to the effectiveness of screening and multidisciplinary treatment. 1 Definitive surgery, meaning colectomy with or without metastasectomy, is the backbone of the multidisciplinary treatment of CRC. The short-term outcomes and long-term survival of patients with CRC who undergo definitive surgery have demonstrated remarkable improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Traditionally, primary colorectal cancer (CRC) stage, hepatic tumor size, number of CRLMs, presence of extrahepatic disease and pre-hepatectomy carcinoembryonic antigen (CEA) levels have been reported to be independent predictors of long-term survival after resection. [4][5][6][7] In addition, CEA levels are widely used to monitor tumor recurrence following resection of CRC and CRLM.…”
Section: Introductionmentioning
confidence: 99%